A dead sense of time: reflections on architecture, history and perception - Basson, Steve (University of Sydney, 2004)
Our current conception of architectural history's normative possibilities return to the emergent surfaces of the eighteenth and nineteenth centuries where they crystallized around a conceptual framework expressive of a logical, progressive and trans-historical vision of time. But there is nothing inevitable about this perspective, or absolute. When Bergson spoke of the absurdity of teleology, Nietzsche of the congenital defects of the aeterna veritas, or Benjamin of the storm and violence of progress, the certainties of that legacy were compromised. In particular, the impact of such dissention upon the conventional space of architectural history would expose a realm of pure ends, a past that always presupposed its present and a future conceived through a blind lens of infinite perfection. What could also be said to reside in the wake of that same rational, continuous and periodized journey across the surfaces of architectures past, is a broad trail of destruction left by denying any autonomy of voice or contextual conditions of prior architectural identity. And yet, despite such questions of legitimacy, the gaze of architectural history remains focused upon a traditional view of time. Here there is no appetite for contestation or release, merely indifference, incomprehension or derision. But why such devotion to a marginalized conception of the past? Does such intransigence reflect a failure to recognize or fully articulate the limits of our traditional engagement with history; an innate desire for the security of familiarity and certitude; or perhaps from fear of an alternative and its potential dynamic of fragmentary, random and terminal moments of past architectural possibility. These issues that surround the historical authority and perception of architectures historical subject are pursued through the following considerations.